Penerapan Media Interaktif Berbasis Game Based Learning Dengan Platform Kahoot Pada Materi Kimia Hijau Untuk Meningkatkan Hasil Belajar Siswa - Karundeng, Fillioni; Rampe, Meytij; Gumolung, Dokri (Chemistry Department, Universitas Negeri Manado, 2025)
Students need more creative and innovative media and methods to support learning activities, namely interactive media and game methods that stimulate students to be more active in learning. This research is aimed at improving student learning outcomes through the application of interactive Game Based Learning media with the Kahoot platform on green chemistry material. This research uses a classroom action research method with 4 stages used, namely planning, implementing actions, observing and reflecting; The results of implementing interactive media based on game based learning with Kahoot showed an increase in learning outcomes, the results of the final test in cycle 1 were 37.5% student completeness and in cycle II there was 87.5% student completion. In conclusion, the application of interactive media based on game based learning can improve student learning outcomes.